2012
DOI: 10.7824/rbh.v11i1.144
|View full text |Cite
|
Sign up to set email alerts
|

Controle de Macroptilium lathyroides com herbicidas aplicados em pré e pós-emergência

Abstract: Resumo-A espécie Macroptilium lathyroides (feijão-de-rôla) foi encontrada infestando áreas relativamente extensas de cultivo de soja na região Sul do Mato Grosso do Sul, onde produtores se queixaram da falta de eficiência de controle de herbicidas. Não existe nenhum herbicida registrado para o controle da espécie, e o número de pesquisas envolvendo a suscetibilidade a diversos princípios ativos é limitado. Objetivou-se com este estudo verificar a eficiência do herbicida glyphosate, isolado ou em associação a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The increase in the accumulation of shikimate and in the absorption, cell penetration, and translocation of glyphosate as a result of adding herbicides that inhibit PPO may explain the increased efficacy of the mixture glyphosate + carfentrazoneethyl under full sunlight conditions. Concenço et al (2012) observed that the application of glyphosate alone was effective in the control of weeds even when it was performed at a later stage; however, carfentrazone-ethyl was only effective when applied after initial emergence. In the present study, the herbicides were applied whilst the plants were budding, which may be the reason for the poor control of M. atropurpureum observed when carfentrazone-ethyl was applied.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the accumulation of shikimate and in the absorption, cell penetration, and translocation of glyphosate as a result of adding herbicides that inhibit PPO may explain the increased efficacy of the mixture glyphosate + carfentrazoneethyl under full sunlight conditions. Concenço et al (2012) observed that the application of glyphosate alone was effective in the control of weeds even when it was performed at a later stage; however, carfentrazone-ethyl was only effective when applied after initial emergence. In the present study, the herbicides were applied whilst the plants were budding, which may be the reason for the poor control of M. atropurpureum observed when carfentrazone-ethyl was applied.…”
Section: Resultsmentioning
confidence: 99%
“…This is an annual with erect growth, up to 1.5 m height, used for conservation of degraded areas and animal feed (Fuentes et al, 2010;Castell-Puchades et al, 2016). However, due to its wide adaptability (found in areas with low and erratic rainfall and flooding conditions), short reproductive cycle, and nonlimiting seed availability, it has been reported as a weed, mainly in soybeans, rice, and guava (Concenco et al, 2012;Ciotti et al, 2014;Hoyos et al, 2015;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized as a legume with great nitrogen fixing capacity, and can be used as green fertilizer (Lorenzi, 2000); In several regions of Brazil it is used as forage for grazing (Vasconcelos et al, 2011). However, M. lathyroides has become a problematic invasive plant for soybean and maize crops and pasture areas (Concenço et al, 2012), due to its characteristics of adaptability to different environments and short reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%